The Effect of the Gap Spark Plug Electrode to The Performance of Motorcycle GL 200 D - Riza Muharni; Ade Ari Agasi; Muchlisinalahuddin Muchlisinalahuddin; Dytchia Septi Kesuma; Ade Usra Berli (Department of Mechanical Engineering, Universitas Andalas, 2022)
The spark plug electrode gap is a narrow distance between the center of electrode and the mass of electrode. This gap has a very big influence on the performance of the gasoline motor. If the spark plug electrode gap is not adjusted correctly or too tight, it will result the spark produced be weaken and the power generated will decrease, meanwhile if the spark plug electrode gap is too wide, it will cause to combustion failure while operate with high rpm. In this research, the effect of the spark plug electrode gap (0.6 mm,0.7 mm and 0.8 mm) on the GL 200 D motorcycle performance is conducted with different input torque and power. The experimental results show that the maximum torque is 14,75 ft-lbs at 6000 rpm and the maximum power is obtained using 0.7 mm spark plug electrode gap where the maximum power is 19,31 Hp at 8000 rpm.The spark plug electrode gap is a narrow distance between the center of electrode and the mass of electrode. This gap has a very big influence on the performance of the gasoline motor. If the spark plug electrode gap is not adjusted correctly or too tight, it will result the spark produced be weaken and the power generated will decrease, meanwhile if the spark plug electrode gap is too wide, it will cause to combustion failure while operate with high rpm. In this research, the effect of the spark plug electrode gap (0.6 mm,0.7 mm and 0.8 mm) on the GL 200 D motorcycle performance is conducted with different input torque and power. The experimental results show that the maximum torque is 14,75 ft-lbs at 6000 rpm and the maximum power is obtained using 0.7 mm spark plug electrode gap where the maximum power is 19,31 Hp at 8000 rpm.